THE USE OF PALBOCKLIB, A CYCLINE-DEPENDENT KINASE 4/6 INHIBITOR, IN THE TREATMENT OF METASTATIC BREAST CANCER. A COST-CONSEQUENCE ANALYSIS - S. L. Pavlinsky; P. I. Shabalkin (Сибирский онкологический журнал)
A new generation of aromatase inhibitors and target therapy directed at cycline-dependent kinases 4 and 6 gives a new opportunity to treat metastatic breast cancer. However, the cost of innovative therapy remains high. We present results of the cost-consequence analysis of combination therapy with fulvestrant and palbociclib compared to fulvestrant monotherapy or combination of exemestan and everolimus as a second-line therapy for metastatic breast cancer. It was shown that the combination therapy involving palbociclib increased the length of quality-adjusted life by 191 days and overall survival by almost a year. The use of palbociclib increased the length of quality-adjusted life by 0.06 QALY compared to the combination arm consisting of everolimus. The cumulative 10 year cost per patient was equal to 5.3 million rubles for combination therapy with palbociclib and 3.5 million rubles for combination therapy with everolimus.